2013
DOI: 10.1186/1471-2148-13-160
|View full text |Cite
|
Sign up to set email alerts
|

Localized versus generalist phenotypes in a broadly distributed tropical mammal: how is intraspecific variation distributed across disparate environments?

Abstract: BackgroundThe extent of phenotypic differentiation in response to local environmental conditions is a key component of species adaptation and persistence. Understanding the structuring of phenotypic diversity in response to local environmental pressures can provide important insights into species evolutionary dynamics and responses to environmental change. This work examines the influence of steep environmental gradients on intraspecific phenotypic variation and tests two hypotheses about how the tropical soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 83 publications
1
19
0
1
Order By: Relevance
“…Recent cross‐species eco‐morphological comparisons demonstrated that temperature, precipitation and productivity affect the distribution of mammal body size and shape in tropical regions (Rodríguez et al ., ; Martínez & Cola, ; Cardini et al ., ). Yet, studies addressing this question at the intraspecific level are still rare (Cardini et al ., ; Marchán‐Rivadeneira et al ., ; Alvarado‐Serrano et al ., ; O'Keefe et al ., ), and, until now, non‐existent for the Atlantic forest fauna.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent cross‐species eco‐morphological comparisons demonstrated that temperature, precipitation and productivity affect the distribution of mammal body size and shape in tropical regions (Rodríguez et al ., ; Martínez & Cola, ; Cardini et al ., ). Yet, studies addressing this question at the intraspecific level are still rare (Cardini et al ., ; Marchán‐Rivadeneira et al ., ; Alvarado‐Serrano et al ., ; O'Keefe et al ., ), and, until now, non‐existent for the Atlantic forest fauna.…”
Section: Discussionmentioning
confidence: 99%
“…Random processes related to genetic drift and gene flow have been implied in human skull variation (Relethford, 1994), despite recent evidence of strong influence of non-random factors (Perez & Monteiro, 2008). Moreover, an intraspecific study of Akodon mollis demonstrated limited morphological differentiation related to ecological variables, yet found that genetic variables explained a small percentage of skull size and shape variation (Alvarado-Serrano et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables were selected based on intraspecific and crossspecies studies that showed these variables are correlated with skull and mandible shape variation in mammals (temperature and temperature seasonality: Martínez and Cola 2011, Cáceres et al 2014, Martínez et al 2014, Meloro et al 2014elevation: Alvarado-Serrano et al 2013, primary productivity: Cardini et al 2007; land cover or vegetation type: Monteiro et al 2003, Alvarado-Serrano et al 2013). Variables were selected based on intraspecific and crossspecies studies that showed these variables are correlated with skull and mandible shape variation in mammals (temperature and temperature seasonality: Martínez and Cola 2011, Cáceres et al 2014, Martínez et al 2014, Meloro et al 2014elevation: Alvarado-Serrano et al 2013, primary productivity: Cardini et al 2007; land cover or vegetation type: Monteiro et al 2003, Alvarado-Serrano et al 2013).…”
Section: Environmental and Spatial Variablesmentioning
confidence: 99%